The metabolic plasticity of B cells - Vivas-García, Yurena; Efeyan, Alejo (Frontiers in Molecular Biosciences, 2022)
The humoral response requires rapid growth, biosynthetic capacity, proliferation and differentiation of B cells. These processes involve profound B-cell phenotypic transitions that are coupled to drastic changes in metabolism so as to meet the extremely different energetic requirements as they transition from resting to an activated, highly proliferative state and to plasma or memory cell fates. Thus, B cells undertake a multi-step, energetically dynamic process that relies on profound metabolic rewiring from low ATP production, to transient and large increments of energy expenditure that depend on high uptake and consumption of glucose and fatty acids. Such metabolic plasticity is under tight transcriptional and post-transcriptional regulation. Alterations in B-cell metabolism driven by genetic mutations or by extrinsic insults impair B-cell functions and differentiation and may underlie the anomalous behavior of pathological B cells. Herein, we review molecular switches that control B-cell metabolism and fuel utilization, as well as the emerging awareness of the impact of dynamic metabolic adaptations of B cells throughout the different phases of the humoral response.